Analyzing the policy-driven adaptation of Important Agriculture Heritage Systems to modernization from the resilience perspective: a case study of Qingtian Rice-Fish Culture System, China - Jiao, Wenjun; Yu, Zhounan; He, Siyuan (Frontiers in Sustainable Food Systems, 2024)
Formulating effective conservation and management policies plays a key role in helping Important Agricultural Heritage Systems (IAHS) cope with the threats and challenges brought by modernization. An important criterion to measure their effectiveness is whether they maintain or enhance the resilience of IAHS. In this study, we first integrate IAHS resilience into the social-ecological systems (SES) framework and propose a SES-based analytical framework for IAHS resilience, which helps analyze how IAHS adapt to external disturbances under the drivers of policies. Then, we suggest the trade-off of ecosystem services as the surrogate of IAHS resilience and use the the carbon footprint per unit output value as an indicator to quantify IAHS resilience. The application in Qingtian Rice-Fish Culture System (QRFCS) reveals that the rice-fish culture systems in three villages have formed different development models driven by different conservation and management policies when challenged by modernization, and have displayed different resilience in different development models. The development model centering on enlarged-scale fish farming in Xinpeng Village has shown the highest resilience; the development model with a combination of moderate-scale land management and experiential heritage tourism in Longxian Village has displayed a moderate resilience; and the development model with organic rice-fish culture integrated into terrace sightseeing tourism in Xiaozhoushan Village has shown the lowest resilience.Based on this, we put forward suggestions for maintaining and enhancing the resilience of QRFCS, so as to improve the management of the heritage system. We present that the results will not only enrich the resilience study of SES, but also promote IAHS management and regional sustainable development.